2021
DOI: 10.1021/acs.jpcc.0c09044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Stability and Recrystallization Behavior of Amorphous Zinc Phosphate

Abstract: Zinc phosphate, an important pigment in phosphate conversion coatings, forms protective films on rubbing surfaces. We have simulated the underlying reactions under shear by ball-milling zinc phosphate and monitored the reaction of hopeite (Zn 3 (PO 4 ) 2 •4H 2 O) and the retarded recrystallization of the amorphous reaction product by powder X-ray diffraction (PXRD) and quantitative infrared (IR) spectroscopy. Abrasion of stainless steel was simulated by addition of pure 57 Fe. The results provide insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Furthermore, the sizes of crystalline MW-OCNT@ZIF-8 and Si­(MW-OCNT@ZIF-8) particles are 24.7 and 26.1 nm, respectively, which are obtained by eq . Finally, regarding the MW-OCNT@ZIF-8-Phosphate nanopowder, there is a broad peak in the range of 25 to 35°, which corresponds to amorphous zinc phosphate, indicating that the phosphate doping has been successfully done on the MW-OCNT@ZIF-8 nanoparticles. , …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the sizes of crystalline MW-OCNT@ZIF-8 and Si­(MW-OCNT@ZIF-8) particles are 24.7 and 26.1 nm, respectively, which are obtained by eq . Finally, regarding the MW-OCNT@ZIF-8-Phosphate nanopowder, there is a broad peak in the range of 25 to 35°, which corresponds to amorphous zinc phosphate, indicating that the phosphate doping has been successfully done on the MW-OCNT@ZIF-8 nanoparticles. , …”
Section: Resultsmentioning
confidence: 93%
“…Finally, regarding the MW-OCNT@ZIF-8-Phosphate nanopowder, there is a broad peak in the range of 25 to 35°, which corresponds to amorphous zinc phosphate, indicating that the phosphate doping has been successfully done on the MW-OCNT@ZIF-8 nanoparticles. 33,34 3.1.2. FTIR Analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Broad resonances at 8.5 ppm could be assigned to amorphous Zn phosphate hydrates ( e.g. , Zn 3 (PO 4 ) 2 ·2H 2 O and Zn 3 (PO 4 ) 2 ·4H 2 O), which suggested that the addition of Zn to the MPC system contributed to the formation of low-crystallinity Zn phosphate hydrates in addition to the crystallized Zn phosphate hydrates and MgKPO 4 ·6H 2 O . Small peaks with low density at 5.5 ppm from crystalline MgKPO 4 ·6H 2 O and Zn 3 (PO 4 ) 2 ·4H 2 O were detected in M/P3–2M8Z, M/6–5M5Z, and M/P6–2M8Z samples, indicating a changed orthophosphate environment. , Overall, it could be deduced that incorporating Zn suppressed the formation and crystallization of MgKPO 4 ·6H 2 O in the MPC system, where Zn reacted with phosphate to form crystalline Zn 3 (PO 4 ) 2 ·4H 2 O and a small amount of amorphous Zn phosphate hydrates.…”
Section: Resultsmentioning
confidence: 99%
“…Isostructural sharp peaks centered at 5.5 ppm in 31 P NMR spectra of M/P3−M, M/P3−5M5Z, and M/P6− M samples corresponded to MgKPO 4 •6H 2 O and Zn 3 (PO 4 ) 2 • 4H 2 O (Figure 2c). 18 Broad resonances at 8.5 ppm could be assigned to amorphous Zn phosphate hydrates (e.g., Zn 3 (PO 4 ) 2 •2H 2 O and Zn 3 (PO 4 ) 2 •4H 2 O), 41 which suggested that the addition of Zn to the MPC system contributed to the formation of low-crystallinity Zn phosphate hydrates in addition to the crystallized Zn phosphate hydrates and MgKPO 4 •6H 2 O. 39 Small peaks with low density at 5.5 ppm from crystalline MgKPO 4 •6H 2 O and Zn 3 (PO 4 ) 2 •4H 2 O were detected in M/P3−2M8Z, M/6−5M5Z, and M/P6−2M8Z samples, indicating a changed orthophosphate environment.…”
Section: Resultsmentioning
confidence: 99%
“…Soft chemistry methods involving hydrated phosphate synthesis have recently drawn attention in a variety of fields from cement engineering to biomaterial and energy applications. 16–19 Among them, one can mention the chemical reaction via coacervation that has been applied for electrical sealing or biomaterial applications. 20,21 Starting from a Graham salt (Na(PO 3 ) n ) solution, the coacervation process consists of promoting the liquid–liquid phase separation thanks to the presence of long phosphate chains which leads to the formation of a phosphate gel called “coacervate” and a supernatant phase.…”
Section: Introductionmentioning
confidence: 99%